Precedentes judiciais obrigatórios e princípio da legalidade: coerência e integridade na construção de respostas adequadas à constituição - Silva Júnior, Denarcy Souza e (2017)
This thesis will aim to to approach the premises of Ronald Dworkin’s Law as integrity to the interpretative paradigm of the jurisdictional precedents, understanding them as texts suscetible of interpretation, moving away from the always present temptation to use the precedents as a way to simply accelerate the decision-making process (quantitative deficit), neglecting to take seriously the arguments of the subjects of the process and to dialogue with them, in attention to the guarantee of the contraditor ando f the motivation of the jurisdictional decisions (qualitative deficit). We won’t analyse the precedent, only, in the light of an eventual legal security or decision’s previsibility, but also as an important tool to the limitation of the jurisdictional discretion in the decision-making process, imposing that, for cases alike, the same patterns are used, forbidding ad hoc decisions that doesn’t relate to the institutional history of the law, in the quest for the correct answer. Integrity and coherence will be taken in this investigation as hermeneutic Keys to the comprehension of the law as a whole, and not only to the civil procedural law or for the jurisdictional precedents. The Public Force has the duty to treat everyone with equal concern and respect, and that doesn’t only mean the repetition of equal decisions, but, moreover, understanding the jurisdictional decision as an act, not of choice, but of political responsability. In this perspective, the quest for right answers is an imperative of the legal theory, which have in the precedents an indispensable tool to the fairness of the decision. To think law as tradition, and having the pre-comprehension of a limitation of the jurisdictional discretion (absence of the degree zero of meaning), moving away from subjectivisms and decisionisms is the grounds of this thesis, that will adopt the theory of justice of Ronald Dworkin as a theoretical referential, but not in an acritic manner and not without trying to adequate it to the dificulties of a country that is adept to the civil law tradition.